2016
DOI: 10.15419/bmrat.v3i12.139
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis C virus infections among the general population of Buner, Khyber Pakhtunkhwa, Pakistan

Abstract: Introduction: In the current study, prevalence of hepatitis C virus and its routes of transmission were determined in district Buner, Khyber Pakhtunkhwa, Pakistan. Methods: Total 230 blood samples for HCV were collected from 7 tehsils of District Buner. Diaspot rapid HCV strips manufactured by Diaspot diagnostic USA were used for the detection of HCV-Ab in the blood. Results: Out of 230 blood samples collected from patients, 158 were found positive for HCV infection. Of the 158 positive cases, 102 (64.55%) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…This study is in line with the study of Arshad, Arshad et al who reported 4.5% prevalence in male and 2% in female [17]. ul Huda et al and Akhtar et al Higher also reported higher HCV prevalence in male than female ul Huda, Jameel [18], [19]. High prevalence in male is attributed to social mobility and freedom, exposing male to risk factors more than female.…”
Section: Discussionsupporting
confidence: 90%
“…This study is in line with the study of Arshad, Arshad et al who reported 4.5% prevalence in male and 2% in female [17]. ul Huda et al and Akhtar et al Higher also reported higher HCV prevalence in male than female ul Huda, Jameel [18], [19]. High prevalence in male is attributed to social mobility and freedom, exposing male to risk factors more than female.…”
Section: Discussionsupporting
confidence: 90%
“…This widespread genetic variability, and mutation tendency has delayed vaccine availability. 10 HCV is highly endemic in the various regions of Pakistan, the exact prevalence rate of HCV infection is still unknown, different reports revealed that 4.8% of population is infected with HCV infection. 11 Understanding HCV epidemiology in Pakistan is critical in developing and targeting cost-effective prevention and treatment intervention against HCV, to meet the global target of HCV elimination.…”
Section: Introductionmentioning
confidence: 99%
“…A Previous study reported that 13.7% of population is infected with HCV infection in district Buner. 12 It is worthy to investigate HCV frequency and distribution of HCV genotypes in tehsil daggar district Buner, KP Pakistan, where detection and genotype determination is insignificant. Consequently, the present study was undertaken to analyze the distribution pattern of HCV genotypes as well as their prevalence and risk factors, and routes of transmission in chronic hepatitis C patients of Buner, Khyber Pakhtunkhwa (KP) in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…The precise frequency of hepatitis C is not known uptil now. Different literature showed that 4.8% community is suffering from hepatitis C. 2,11 Epidemiological understanding is important in the development of economical medication against hepatitis C. 12…”
Section: Introductionmentioning
confidence: 99%